The Concept of Radical Responsibility for Non-human Animals - Dzwonkowska, Dominika (Frontiers in Psychology, 2020)
The human–animal relation is a complex one; it involves a collective and individual object and subject as well as synchronic and diachronic responsibility. Due to the range of dimensions that are included into this relation, there is a need for a form of responsibility that covers all forms of it: this is radical responsibility. This form of responsibility claims that we are responsible for what we do and the beneficial actions that others do for us. Moreover, we are responsible for the unintended and unconsidered consequences of our actions and for not taking action when we could prevent something wrong from happening. This radical form of responsibility fully covers the entire range of complex human–animal relations and allows a moral agent to see the wide-ranging moral consequences of his/her actions.